Factors of the Ethos in executives: identity, identification and differentiation. A theoretical approach - Reynoso Espinoza, Deivit Wilfredo (2018)
This article presents in a theoretically way the constructs of identity, identification and diferentation as psychology components of the ethos of the managerial social class of business. Identity is built by the group of characterists which define their members, difference them and allow the categorization of their members. Identification is the process through which every person percibe, adapt and adjust their social habilities with the group. Diferentation is the search of individuality which makes every one different from the others at the same time it adjust their differences to live with others. This are some of the main components to describe the Ethos of a social class. This constructs helps to find a definition of the subyacent boundiries which legitimice some conducts at intra group.